THE ACCESS RATE TO DIAGNOSIS AND TREATMENT MODALITIES IN BREAST CANCER PATIENTS IN TURKEY; MULTICENTER OBSERVATIONAL STUDY - Pınar Saip; Serkan Keskin; Metin Özkan; Mehmet Ali Kaplan; Fatma Aydoğan; Güzin Gönüllü Demirağ; Sernaz Uzunoğlu; Hüseyin Engin; Gül Başaran; Nilüfer Güler; Kazım Uygun; Binnaz Demirkan; et al. (European Journal of Breast Health, 2011)

(untitled)
Purpose:We aimed to determine the elapsed time between the first notification of the disease and the accession to the diagnosis and treatment modalities and its associated factors in female patients with breast cancer in Turkey.Patients and Methods:The data was acquired by a questionnaire completed by 535 patients who applied to the 14 various oncology clinics between 1st and 28th of February 2010 in Turkey. The centers located in metrople -Istanbul, Izmir, and Ankara- were named Group 1 (n=161), the centers located in Marmara and Central Anatolia region -Kocaeli, Bursa, Edirne and Kayseri- were named Group 2 (n=189), and the centers located in Karadeniz and East-Southeast Anatolia region -Zonguldak, Samsun, Trabzon, Elazig and Diyarbakir- were named Group 3 (n=185). The grouping for the centers were configured according to their socio-economic development of provinces.Results:Median age was 48 ± 11.2 (24–89) years, the number of patients of age less than 50 years were 282 (%56.1). 85% of the patients detected a mass in their breast by themselves. %27 of the patients over age 50 never had a breast ultrasound and/or mammography done until the definite diagnosis was established. The median elapsed time between the disease noticed by the patient and the application to a health care center was 10 days, between the application and the biopsy was 19 days, between the biopsy and the surgery was 31 days. The elapsed time between recognition of the disease by the patient and the patient applying to a health care center in Group 1, Group 2, and Group 3 was 15, 10 and 14 days, respectively, and the elapsed time between the biopsy and surgery was 14, 1.5 and 12 days, respectively. The elasped time between the first recognition of the disease and applying of the patient to the health care center and the elapsed time between the biopsy and surgery in Group 2 centers was statistically significantly shorter compared to group 1 and 3 centers (p<0.05).Conclusions:A high level of awareness of breast cancer in our country has examined through the time that is defined as 10 days between recognition of the disease and medical application. Compared with the developed countries the elapsed time between the application and biopsy, surgery and systemic therapy is longer than the expected and it has been marked differences between regions.